Value-added products from wastewater reduce irrigation needs of Arundo donax energy crop. (December 2021) - Cano-Ruiz, J.; Ruiz Fernández, J.; Alonso, J.; Mauri, P.V.; Lobo, M.C.
Abstract: Irrigation restrictions due to drought periods related to climate change, would affect different crops, especially to non-food crops. In this regard the effect of irrigation reduction should be studied in energy crops in order to obtain a sustainable bioenergy cropping system. Arundo donax, has been considered a crop with high water requirements, it has nevertheless been proven to be drought tolerant. However, there is a lack of knowledge on the effect of reduced irrigation combined with the use of different fertilizers. This work studied the combined effect of value-added products (VAPs) from wastewater (treated sewage sludge) or traditional inorganic fertilizers, and irrigation reduction in Arundo donax crop in a 2-year pot experiment. Plant biometric characteristics, chemical properties and biomass yield were studied as well as the effect of treatment on soil properties. Results showed that under reduced irrigation conditions, biomass production was reduced, especially during the second year. Organic treatments from sewage sludge minimize the effect of irrigation reduction. In these treatments, biomass yield for reduced irrigation was similar to that of the control treatment with irrigation at field capacity. For this reason, it is recommended to use VAPs from wastewater as organic amendments enabling water restriction with lower effect on Arundo production. Graphical abstract: Image 1 Highlights: Treated sewage sludge is a value-added product (VAP) that reduces water needs for Arundo. VAPs application to soil increase Arundo donax biomass and heating value. Recycling sewage sludge as amendment contributes to protect soil against degradation. VAP from wastewater treatment constitute an adequate soil management for Arundo production.